2018
DOI: 10.1007/s13361-018-2079-7
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Ion/Ion Chemistry as a Probe for the Presence of Carboxylate Groups in Polypeptide Cations

Abstract: The reactivity of 1-hydroxybenzoyl triazole (HOBt) esters with the carboxylate functionality present in peptides is demonstrated in the gas phase with a doubly deprotonated dianion. The reaction forms an anhydride linkage at the carboxylate site. Upon ion trap collisional induced dissociation (CID) of the modified peptide, the resulting spectrum shows a nominal loss of the mass of the reagent and a water molecule. Analogous phenomenology was also noted for model peptide cations that likely contain zwitterionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Gas-phase covalent labeling via ion/ion reactions inside of mass spectrometers has been demonstrated for peptides [27][28][29] and the protein ubiquitin under denaturing conditions [30][31]. These reactions require the presence of an electrostatically "sticky" group to anchor the reagent to the protein to form a long lived complex.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas-phase covalent labeling via ion/ion reactions inside of mass spectrometers has been demonstrated for peptides [27][28][29] and the protein ubiquitin under denaturing conditions [30][31]. These reactions require the presence of an electrostatically "sticky" group to anchor the reagent to the protein to form a long lived complex.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ion/ion reactions were applied to native ubiquitin ions in order to assess the three-dimensional structure and relative reactivity of residue side chains in the gas phase. Singly deprotonated sulfo-benzoyl-HOAT was used due to its lower barrier for covalent reaction in the gas phase relative to NHS esters (18 kcal/mol vs. 21 kcal/mol, respectively), with the ability to react with lysine, arginine, histidine, aspartate, and glutamate [31,33]. Figure 6 A shows the ion/ion reaction of ubiquitin 6 + and sulfo-benzoyl-HOAT -.…”
Section: Interrogating Native Ubiquitin With Ion/ion Reactionsmentioning
confidence: 99%
“…12 coupled to IM-MS/MS can, in principle, provide for the threedimensional characterization of gaseous protein ions. 23,24 Though most CLMS approaches have relied on "bottom-up" proteomics, utilizing enzymatic digestion to enable the identification of modification sites, the "top-down" approach in proteomics was developed in order to obtain primary structural information directly from the gas-phase dissociation of intact protein ions without the need for extensive separations or digestion prior to MS/MS analysis. 25 During a typical "top-down" experiment, protein identification is made by analyzing the sequence fragments of intact proteins from tandem MS, which allows for the examination of the entire amino acid sequence, thereby characterizing intact proteins and identifying the number and type of post-translational and other modifications in various so-called proteoforms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…By using bifunctional reagents that form a long-lived complex (due to a relatively high-energy dissociation barrier via, e.g., gas-phase salt bridge formation, that allows for significant collisional cooling) and contain moieties that form covalent bonds, such as aldehydes or activated esters, , new covalent bonds can be efficiently formed. More recently, covalent bond formation via ion/ion reactions has been used to characterize gas-phase tertiary structures of protein ions, via covalent chemical cross-linking, covalent labeling, and salt bridge sensitive covalent reactions …”
Section: Introductionmentioning
confidence: 99%
“…More recently, covalent bond formation via ion/ion reactions has been used to characterize gas-phase tertiary structures of protein ions, via covalent chemical crosslinking, 11 covalent labeling, 12 and salt bridge sensitive covalent reactions. 13 Careful measurements using ion mobility−mass spectrometry (IM−MS) approaches have shown that a strong correlation exists between gaseous and solution protein structures, 14−23 especially when unintentional ion heating via energetic collisions or other mechanisms is minimized, and this is supported by molecular dynamics simulations of proteins during and after the electrospray process. 24,25 These observations make gas-phase measurements of protein structures attractive due to the sensitivity, speed, and specificity of MS. 26 Since the time scale of MS experiments dictates that chemistry of gaseous ions is typically under kinetic control, relevant protein structural information can be obtained if isomerization to extended conformations (via, e.g., activating collisions) is minimized or takes place only after structurally sensitive studies are conducted.…”
Section: ■ Introductionmentioning
confidence: 99%